The role of chaperone-mediated autophagy in drug resistance - Ana Beatriz da Silva Teixeira; Maria Carolina Clares Ramalho; Izadora de Souza; Izabela Amélia Marques de Andrade; Isabeli Yumi Araújo Osawa; Camila Banca Guedes; Beatriz Silva de Oliveira; Cláudio Henrique Dahne de Souza Filho; Tainá Lins da Silva; Natália Cestari Moreno; Marcela Teatin Latancia; Clarissa Ribeiro Reily Rocha (Genetics and Molecular Biology, 2024)
Abstract In the search for alternatives to overcome the challenge imposed by drug resistance development in cancer treatment, the modulation of autophagy has emerged as a promising alternative that has achieved good results in clinical trials. Nevertheless, most of these studies have overlooked a novel and selective type of autophagy: chaperone-mediated autophagy (CMA). Following its discovery, research into CMA’s contribution to tumor progression has accelerated rapidly. Therefore, we now understand that stress conditions are the primary signal responsible for modulating CMA in cancer cells. In turn, the degradation of proteins by CMA can offer important advantages for tumorigenesis, since tumor suppressor proteins are CMA targets. Such mutual interaction between the tumor microenvironment and CMA also plays a crucial part in establishing therapy resistance, making this discussion the focus of the present review. Thus, we highlight how suppression of LAMP2A can enhance the sensitivity of cancer cells to several drugs, just as downregulation of CMA activity can lead to resistance in certain cases. Given this panorama, it is important to identify selective modulators of CMA to enhance the therapeutic response.